Application of DSTATCOM coupled with FESS for Power Quality Enhancement and Fault Mitigation - Nada Mamdouh; R.A. Swief; M.A.L. Badr (Renewable Energy and Sustainable Development, 2017)
In power systems, the use of renewable energy, especially Wind power generation is steadily increasing around the world. However, this incorporation and the lack of controllability over the wind, and the type of generation used cause problems in the power quality and in the dynamics of the system. In this work, the use of a Distribution Static Synchronous Compensator (DSTATCOM) coupled with a Flywheel Energy Storage System (FESS) is proposed to mitigate problems introduced by the intermittency of wind power generation. A dynamic model of the DSTATCOM/FESS device is briefly presented and a multi-level control technique is proposed. The proposed control technique has one control mode for active power, and two control modes to choose between, for reactive power and voltage control. The above technique has been used here to enhance not only the steady state operation but also to mitigate sudden load changes. The control system under consideration, with the DSTATCOM/FESS, and its controls are analyzed also, under the conditions of different faults which may happen in the system.  Simulation tests of the device are analyzed when it is combined with wind generation in the electric system. The results demonstrate satisfactory performance of the proposed control techniques, as well as a high effectiveness of the control system to mitigate problems introduced by wind power generation.